Keberagaman Jenjang Kelas Untuk Meningkatkan Efisiensi Tempat, Hasil Dan Aktivitas Belajar Di Sekolah Indonesia Den Haag (SIDH) Belanda - Rakanita Dyah Ayu Kinesti; Haniam maria rizqiya; Dwi Ulis Syaadah; Noor Hidayah; Fuad Khoirul Umam (Universitas Negeri Makassar, 2021)
Teaching and learning activities have standardization in accordance with the Regulation of the Minister of National Education of the Republic of Indonesia Number 24 of 2007 concerning Standard for Facilities and Infrastructure. In fact, the limited facilities and teaching staff are owned by the Sekolah Indonesia Den Haag (SIDH) so that it can affect the teaching and learning process for students. The purpose of this study was to determine the steps taken by the Sekolah Indonesia Den Haag (SIDH) in increasing student learning activities by combining small and large elementary class levels. The research method used is descriptive qualitative. The subjects of this study were the teaching staff and students of the Sekolah Indonesia Den Haag (SIDH) Elementary School with a total of nine regular level students. Combining class levels is a step to improve student learning outcomes and activities by looking at the limitations of class fitness, teaching staff, and students. Finally, the authors conclude that based on the above discussion, there has been a success. In other words, combining class levels in the grouping of small SD and large SD can improve the results and activities of students in classrooms with limited class space.